The Impact of Entrepreneurial Passion and Personality Traits on Hybrid Entrepreneurship in Pakistan: Estimation and Analysis - Majid, Safyan; Wahga, Aqueel Imtiaz; Iqbal, Javeed (Annals of Human and Social Sciences, 2023)
Using a sample of 370 individuals working in different companies in Pakistan, the study highlighted various personality traits and human abilities that influence hybrid entrepreneurship. The study is built on the theoretical framework of planned behaviour that aims to explain and predict human behaviour in a variety of contexts. Considering the current economic turmoil in Pakistan, it is crucial to understand the dynamics of human behaviour that can foster entrepreneurial activities which can alleviate poverty and increase the income level of the individual. The study employed partial least square to determine the impact of entrepreneurial passion, opportunity recognition ability, resource allocation ability and entrepreneurial resources on the hybrid entrepreneurial intention. The research provides significant imply that personality traits and entrepreneur’s ability to allocate resource, recognize opportunities and possess resources in the models to understand hybrid entrepreneurial behavior, moreover, policy makers should account these factors in devising any entrepreneurial policy analysis.